SARS-CoV-2 Genomes From Oklahoma, United States - Narayanan, Sai; Ritchey, John C.; Patil, Girish; Narasaraju, Teluguakula; More, Sunil; Malayer, Jerry; Saliki, Jeremiah; Kaul, Anil; Agarwal, Pratul K.; Ramachandran, Akhilesh (Frontiers in Genetics, 2021)
Genomic sequencing has played a major role in understanding the pathogenicity of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). With the current pandemic, it is essential that SARS-CoV-2 viruses are sequenced regularly to determine mutations and genomic modifications in different geographical locations. In this study we sequenced SARS-CoV-2 from 5 clinical samples obtained in Oklahoma, USA during different time points of pandemic presence in the state. One sample from the initial days of the pandemic in the state and 4 during the peak in Oklahoma were sequenced. Previously reported mutations including D614G in S gene, P4715L in ORF1ab, S194L, R203K and G204R in N gene were identified in the genomes sequenced in this study. Possible novel mutations were also detected such as G1167V in S gene, A6269S and P3371S in ORF1ab, T28I in ORF7b, G96R in ORF8. Phylogenetic analysis of the genomes showed similarity to viruses from across the globe. These novel mutations and phylogenetic analysis emphasize the contagious nature of the virus.